Analisis Faktor Penyebab Terjadinya Anemia pada Ibu Hamil di Wilayah Kerja Puskesmas Kalodran Kota Serang Provinsi Banten - Susi Irianti (Pusat Riset dan Inovasi Nasional, 2023)
Anemia in pregnancy is a national problem because it reflects the value of the socio-economic welfare of the community and has a very large influence on the quality of human resources. where in this situation the patient does not go on a diet against anemia. The purpose of this study was to find out the description of the factors that cause anemia in pregnant women in the Kalodran Community Health Center, Serang City, Banten Province in 2022. Descriptive research and this study used primary data with measuring instruments, namely questionnaires that have been tested with instruments, in data analysis using the Chi Square statistical test with a sample of pregnant women as many as 44 respondents and researchers chose respondents with total sampling technique. The description of economic status is mostly low <UMR as much as 34 (77.3%), the knowledge of pregnant women about anemia is mostly lacking is as many as 31 (<70.5%), the education of pregnant women is mostly medium as much as 33 (75%), Compliance with consumption of Fe tablets was mostly disobedient as much as 34 (77.3%), parity was mostly multipara as many as 33 (75%), most pregnant women were <25 years old as many as 28 (63.6%), husband support was partially 28 (63.6%) did not get husband's support, there was a relationship between socio-economic, knowledge, education, adherence to consuming FE tablets, parity, age, and husband's support with the occurrence of anemia in pregnant women in the Kalodran Health Center area, Serang City, Banten Province. 2022. It is recommended for future researchers that the results of this study will add references to knowledge and insight regarding the incidence of anemia in pregnant women so that students can gain skills in handling cases of anemia in pregnant women. as well as being able to apply the science of research methodology that has been studied in the form of a thesis.